Analysis of Prevention of Unscheduled Campaigns Carried out by Election Monitoring Institutions in 2024 - Ramadani, Alfariq; Palevi, Bintang Rheza; Muhammad Randianto (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
The research was conducted due to the phenomenon of campaign start theft by political parties in Indonesia. The goal of this study was to understand the preventive measures taken by Bawaslu to address campaign kick-off theft on social media. The research employed a qualitative method, describing the investigated phenomenon. It utilized a literature review approach, collecting relevant literature and using documentation data collection techniques, including gathering books, articles, and regulations related to digital campaign monitoring. The findings indicate that some political parties still engage in social media (Instagram) campaigns, and there is a lack of legal clarity regarding sanctions for election participants involved in campaign kick-off theft.